Steam jet ejector cooling powered by low grade waste or solar heat - Meyer, Adriaan Jacobus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2006.